Designing A Web-Based Bicycle Modification Sales System - Tiyo Haryo Subaktiono; Arham Jusni Indrawan; Nadya Nurul (International Journal of Research and Applied Technology (INJURATECH), 2023)
Bike modification is one of the activities for bicycle enthusiasts. This modification can be interpreted as changing certain parts of one type of bicycle for various user needs. However, not all workshops have complete components to produce optimal modifications, so customers have to look to several workshops to get them. This proposal aims to design a website-based application system that functions as a place for selling bicycle components or ordering home service services in installing components or modifying bicycles. The research method used in this research is descriptive analysis with a qualitative approach. The results of the research are the formation of a website-based sales system to sell various bicycle components and provide home service services that can be accessed on various consumer devices. The main concept of this website is a price list of bicycle components. In it there is a search feature to find bicycle components that consumers want to order and there is a bicycle modification recommendation feature that helps consumers to make bicycle modifications. In addition, this website has a home service feature for component installation or bicycle modification and has an e-payment or electronic payment feature to facilitate the transaction process. Therefore, a sales system like this will facilitate bicycle users in meeting their needs.